Copy Number Variation Analysis of Euploid Pregnancy Loss - Gu, Chongjuan; Gao, Huan; Li, Kuanrong; Dai, Xinyu; Yang, Zhao; Li, Ru; Wen, Canliang; He, Yaojuan (Frontiers in Genetics, 2022)
Objectives: Copy number variant (CNV) is believed to be the potential genetic cause of pregnancy loss. However, CNVs less than 3 Mb in euploid products of conceptions (POCs) remain largely unexplored. This study aims to investigate the features of CNVs less than 3 Mb in POCs and their potential clinical significance in pregnancy loss/ fetal death. Methods: CNV data were extracted from a cohort in our institution and 19 peer-reviewed publications, only those CNVs less than 3 Mb detected in euploid pregnancy loss/fetal death were included. We conducted a CNV map to analyze the distribution of CNVs in chromosomes using R packages karyoploteR_1.10.5. Gene names and annotated gene types covered by those CNVs were mined from the human Release 19 reference genome file and GENECODE database. We assessed the expression pattern and the consequences of murine knock-out of those genes using databases TiGER and Mouse Genome Informatics (MGI). Functional enrichment and pathway analysis for genes in CNVs were performed using clusterProfiler V3.12.0. Result: Breakpoints of 564 CNVs less than 3 Mb were obtained from 442 euploid POCs, with 349 gains and 185 losses. The CNV map showed that CNVs distributed in all chromosomes, with the highest frequency detected in chromosome 22 and the lowest frequency in chromosome Y, and CNVs showed a higher density in the pericentromeric and sub-telomeric regions. 5414 genes mined from the CNV regions (CNVRs), Gene Ontology (GO) and pathway analysis showed that the genes were significantly enriched in multiple terms, especially in sensory perception, membrane region and tight junction. 995 protein-coding genes have been reported mammalian phenotypes in MGI and 276 of them result in embryonic lethality or abnormal embryo/placental in knock-out mouse model. CNV located at 19p13.3 was the most common CNV of all cases. Conclusion: CNVs less than 3 Mb in euploid POCs distribute unevenly in all chromosomes and with a higher density in the pericentromeric and sub-telomeric regions. The genes in those CNVRs are significantly enriched in biological processes and pathways that are important to embryo/fetus development. CNV in 19p13.3 and the variations of ARID3A and FSTL3 might contribute to pregnancy loss.